2011
DOI: 10.1017/s0022112011000012
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional vortex dynamics in oscillatory flow separation

Abstract: The dynamics of coherent columnar vortices and their interactions in an oscillatory flow past an obstacle are examined experimentally. The main focus is on the low Keulegan–Carpenter number range (0.2 < KC < 2), where KC is the ratio between the fluid particle excursion during half an oscillation cycle and the obstacle size, and for moderate Reynolds numbers (700 < Rev < 7500). For this parameter range, a periodic unidirectional vortex pair ejection regime is observed, in which the direction of vor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Önder and Yuan (2019) added that the appearance of spanwise flow features, "ribs", is not random and the spanwise wavelength ranges from 0.6λ to 0.9λ, comparable to the spacing of the brick-pattern proposed by Ourmières and Chaplin (2004) and Blondeaux et al (2004). Canals and Pawlak (2011) demonstrated that the vortex cores are unstable to the centrifugal instability, which results in the three-dimensional vortex structures. The spanwise wavelength of the ribs is in the range of two to five times the vortex core radius.…”
Section: Three-dimensionality In Flow Structuresmentioning
confidence: 72%
“…Önder and Yuan (2019) added that the appearance of spanwise flow features, "ribs", is not random and the spanwise wavelength ranges from 0.6λ to 0.9λ, comparable to the spacing of the brick-pattern proposed by Ourmières and Chaplin (2004) and Blondeaux et al (2004). Canals and Pawlak (2011) demonstrated that the vortex cores are unstable to the centrifugal instability, which results in the three-dimensional vortex structures. The spanwise wavelength of the ribs is in the range of two to five times the vortex core radius.…”
Section: Three-dimensionality In Flow Structuresmentioning
confidence: 72%
“…However, spatially varying high levels of turbulence generated as oscillatory flows interact with complex boundaries have been observed in numerous laboratory studies, e.g., Liu et al . [] for flows over ripples, and by Canals and Pawlak [] for a flapping plate.…”
Section: Resultsmentioning
confidence: 99%
“…The back-and-forth motion generates the pair of counterrotating vortex rings that can be seen downstream. Shedding of such vortex pairs, or dipoles [17], has also been observed in other cases of oscillatory flows past an object [18][19][20][21]. The close-up photograph of 033202-5 Fig.…”
Section: Flow Visualizationmentioning
confidence: 83%